KESEJAHTERAAN SUBJEKTIF SEBAGAI PREDIKTOR PERILAKU PROSOSIAL PADA SISWA SMA YANG MENGIKUTI KEGIATAN OSIS - Tiara Fadila Rizqiany; Erik Wijaya (Fakultas Psikologi Universitas Tarumanagara, 2023)
This study aims to determine the relationship between subjective well-being and the prosocial behavior of adolescents who participate in student council activities at the high school level. This study uses a non-experimental correlational quantitative method and the sampling technique uses a purposive sampling technique; convenience sampling. Participants in this study involved 387 student council members at the high school level. The measurement tools used in this study are the subjective well-being scale and the prosocial behavior scale adapted by the Faculty of Psychology, University of Tarumanagara. The analysis used in this study is non-parametric analysis and using the Spearman rho correlation through the SPSS version 15 program. Based on the analysis , the results obtained are r: .215** and p: <.005, the results of this study are that there is a significant relationship between subjective well-being and prosocial behavior in adolescents who participate in student council activities at the high school level.